Efficacy and safety of the dexamethasone implant in vitrectomized and nonvitrectomized eyes with diabetic macular edema: A systematic review and meta-analysis - Yuan, Qiongzhen; Liu, Yanling; Gou, Yueqin; Xu, Hanyue; Gao, Yunxia; Liu, Yilin; Chen, Yi; Zhang, Ming (Frontiers in Pharmacology, 2022)
Purpose: To compare the efficacy and safety of the intravitreal dexamethasone (DEX) implant for the treatment of diabetic macular edema (DME) in vitrectomized and nonvitrectomized eyes. Methods: We performed a literature search in four electronic databases (PubMed, EMBASE, MEDLINE, and Cochrane Library) from inception to May 22, 2022. Studies comparing the efficacy of the DEX implant in vitrectomized and nonvitrectomized eyes with DME with at least 3 months of follow-up were included. The main outcomes included comparison of the mean change in the best-corrected visual acuity (BCVA) and central macular thickness (CMT) from baseline to different follow-up endpoints between the vitrectomized and nonvitrectomized groups. The secondary outcomes were the mean duration of action for the first DEX implantation and the number of required injections throughout the follow-up period. Safety data were collected and compared. Results: The final analysis included 7 studies involving 582 eyes, 208 vitrectomized eyes and 374 nonvitrectomized eyes. The mean between-group differences in BCVA improvement were not significant at any endpoint, with averages difference of -0.07 logarithm of the minimum angle of resolution (logMAR) (p = 0.088) at 1 month, -0.03 logMAR (p = 0.472) 3 months, -0.07 logMAR (p = 0.066) 6 months, and -0.04 logMAR (p = 0.486) 12 months. The mean between-group differences in CMT reduction were not statistically significant, with mean differences of 7.17 μm (p = 0.685) at 1 month, 20.03 μm (p = 0.632) 3 months, -1.80 μm (p = 0.935) 6 months, and -25.65 μm (p = 0.542) 12 months. However, the vitrectomized group had a significantly shorter duration of action during the first DEX implantation than the nonvitrectomized group, with a mean difference of 0.8 months (p = 0.005). No significant between-group differences were detected for the number of required injections or safety profile. Conclusions: This meta-analysis showed similar efficacy and safety of the sustained-release DEX intravitreal implant for vitrectomized and nonvitrectomized eyes with DME. The intravitreal DEX implant could be considered an effective choice for DME treatment in eyes with prior vitrectomy.